Efektivitas Perawatan Luka Modern dan Konvensional terhadap Proses Penyembuhan Luka Diabetik - Muhammad Irwan; Indrawati; Maryati; Risnah; Salmah Arafah (Lembaga Penelitian dan Pengabdian Masyarakat, Universitas Puangrimaggalatung, 2022)
Diabetes mellitus (DM) is a chronic disorder of carbohydrate metabolism. The number of people with diabetes mellitus in the world was recorded at 382 million people suffering from this disease in 2013 and it is estimated that the number will increase significantly to 592 million in 2035. The prevalence of diabetic foot ulcers in patients with diabetes mellitus is between 17-23% and it is estimated that a patient's lifetime can experience foot ulcers up to 25%. 15-30%.. This study aims to analyze the effectiveness of modern and conventional wound care on diabetic wound healing with a quasi-experimental research design with a pre-test post-test control group design. It was carried out in the intervention group at the Ikram Wound Care clinic and the control group at the Majene Hospital Polyclinic in May – July 2019. The sampling technique used nonprobability sampling with the consecutive sampling method. The wound measurement instrument is the Bates-Jensen Wound Assessment Tool (BJWAT). The statistical test used is the